ÉTICA EMPRESARIAL Y RSE: TENDENCIAS DESDE CHILE - Suárez, Andrés (2010)
The subject of this article is to illustrate some trends in Corporate Social Responsibility (CSR), in the Latin America countries and, more specifically, in Chile. Some practices in CSR, such as the publishing of Sustainability Reports, could exemplify the commitment about the CSR. One could think that there is a direct link between the application of the global standards of CSR and what the companies really do, but it does not occur every time. In a globalised world global organizations, such as the OCDE, can force companies to respect rules in the CSR area and corporate governments, and that is the case in countries such as Mexico and Chile. At the same time, the Social Doctrine of the Church and The Vatican agree with economists such as Joseph Stiglitz about the moral responsibility of corporations. CSR is hard to understand, because it involves areas from different origins, such as the business ethics, on the one hand, and the environmental sustainability, on the other hand. CSR faces two policies. One has an obligatory nature, with strict rules, and the other one is based on the autonomy and consciousness of the business man.